Las canciones infantiles en el desarrollo del lenguaje oral en los niños y niñas de Primero de Básica paralelo “D” en la Escuela de Educación Básica “Dr. Nicanor Larrea” en la ciudad de Riobamba año lectivo 2015-2016 - Moreno Guzmán, Virginia Anabel (2016)
The following work was done at the Elemantary School “Dr. Nicanor Larrea “, in which it was observed that there is a need to develop the ability to communiate orally in children of 5 years old, through children's songs. The objective of this Research was to know the importance of the use of children's songs in the development of oral language, for which it was established as a general objective to know the importance of the use of children's songs in the development of oral language, which consolidated with specific objectives such as analyzing the use of children's songs; explain the relationship between oral language development and the learning process and compare the development of oral language through children's songs. The research design was not experimental because it was established that the correlation between the variables of studies the kind of research was of a documentary type because it relied on bibliographical references and information field, given that the place where they did the research, Elementary school "Dr. Nicanor Larrea ", applied because the study analyzes the real problem. The level of research was diagnostic because we check the fundamental aspects to be considered. The population in the investigation was thirty-six 1st graders "D", the applied technique was through observations, since through observations it was possible to determine how children develop their oral language using children's songs. Once the information was collected, the analysis was performed and interpretation it was possible to establish that children's songs develop oral language in the children. In conclusion, playful children song’s motivate the children to develop a better oral language, learn new words and expand their vocabulary at very early ages.